L Particles Transmit Viral Proteins from Herpes Simplex Virus 1-Infected Mature Dendritic Cells to Uninfected Bystander Cells, Inducing CD83 Downmodulation - Heilingloh, Christiane; Kummer, Mirko; Muehl-Zuerbes, Petra; Drassner, Christina; Daniel, Christoph; Klewer, Monika; Steinkasserer, Alexander (Journal of Virology, 2015)
Mature dendritic cells (mDCs) are known as the most potent antigen-presenting cells (APCs) since they are also able to prime/induce naive T cells. Thus, mDCs play a pivotal role during the induction of antiviral immune responses. Remarkably, the cell surface molecule CD83, which was shown to have costimulatory properties, is targeted by herpes simplex virus 1 (HSV-1) for viral immune escape. Infection of mDCs with HSV-1 results in downmodulation of CD83, resulting in reduced T cell stimulation. In this study, we report that not only infected mDCs but also uninfected bystander cells in an infected culture show a significant CD83 reduction. We demonstrate that this effect is independent of phagocytosis and transmissible from infected to uninfected mDCs. The presence of specific viral proteins found in these uninfected bystander cells led to the hypothesis that viral proteins are transferred from infected to uninfected cells via L particles. These L particles are generated during lytic replication in parallel with full virions, called H particles. L particles contain viral proteins but lack the viral capsid and DNA. Therefore, these particles are not infectious but are able to transfer several viral proteins. Incubation of mDCs with L particles indeed reduced CD83 expression on uninfected bystander DCs, providing for the first time evidence that functional viral proteins are transmitted via L particles from infected mDCs to uninfected bystander cells, thereby inducing CD83 downmodulation.HSV-1 has evolved a number of strategies to evade the host's immune system. Among others, HSV-1 infection of mDCs results in an inhibited T cell activation caused by degradation of CD83. Interestingly, CD83 is lost not only from HSV-1-infected mDCs but also from uninfected bystander cells. The release of so-called L particles, which contain several viral proteins but lack capsid and DNA, during infection is a common phenomenon observed among several viruses, such as human cytomegalovirus (HCMV), Epstein-Barr virus, and HSV-1. However, the detailed function of these particles is poorly understood. Here, we provide for the first time evidence that functional viral proteins can be transferred to uninfected bystander mDCs via L particles, revealing important biological functions of these particles during lytic replication. Therefore, the transfer of viral proteins by L particles to modulate uninfected bystander cells may represent an additional strategy for viral immune escape.
EVALuna2:19522